The Role of Marketplace Policy on Welcome Mat Effects for Children Eligible for Medicaid or the Children's Health Insurance Program - Julie L. Hudson PhD; Asako S. Moriya PhD (SAGE Publishing, 2020)
The Affordable Care Act (ACA) required coordination between Marketplaces, Medicaid, and the Children's Health Insurance Program (CHIP) in an effort to streamline application processes and improve enrollment. We use 2013-2018 data from the American Community Survey and difference-in-difference models to estimate the relationship between Marketplace policy and increases in Medicaid/CHIP coverage observed among pre-ACA eligible children after the implementation of the ACA ("welcome mat effects"). Our sample includes non-disabled, citizen children (0-18) at 139-250% FPL who were Medicaid-/CHIP-eligible before (and after) the implementation of the ACA. Marketplace policies studied include state-based versus federally-facilitated, and whether the Marketplace had authority to directly enroll Medicaid-/CHIP-eligible applicants into public coverage. Models also control for ACA adult Medicaid expansion policy and provide the first estimates in this literature for non-expansion states. Welcome mat effects were present among all Marketplace and expansion policy categories. However, public coverage increased more in states that empowered their Marketplace to enroll publicly-eligible applicants directly into Medicaid/CHIP and these results were driven by enrollment policy, not by choice of state-based versus federal based Marketplaces. Welcome mat effects were largest in expansion states (for most years) and among children whose parents did not hold employer-sponsored insurance coverage. Ranging from 9 to 13 percentage points, these estimates are larger than those found among other subgroups of children in the welcome mat literature. Although there is evidence of lagged effects for both welcome mat effects and the role of Marketplace policy in non-expansion states, by 2018 we find no differences in these measures by expansion policy.